A new cannula for suction removal of parenchymal tissue of gynaecomastia - Gangegowda, Mahesh Siddapura; Prakash, Gagan S.; Ramaiah, Balaji; S. M., Chetan Mali (International Surgery Journal, 2019)
Background: There are various surgical techniques that are available for surgical management of gynecomastia. The aim of the study was to evaluate the cosmetic results and patient satisfaction of a combined liposuction with excision for gynecomastia. Methods: Clinical records of patients affected by gynecomastia referred to our department between between 2015 and 2018 were analyzed, total of 23 patients were included in the study. Results: Overall 23 patients underwent surgery for gynecomastia in the study period, a total of 42 breasts were operated as most of the cases were bilateral in nature. 19 patients had bilateral presentation while 4 patients had unilateral presentation. 35 breasts (80%) were operated with a combined liposuction and excision. Liposuction addresses the fatty gynecomastia whereas open excision is used to remove the glandular enlargement. Four patients underwent excision alone as these patients had a firm retro-areolar lump that was suspicious for malignancy. Another four patients underwent liposuction alone. Conclusions: Surgery is the main stay of management of gynecomastia. Liposuction with excision has had the best outcome with good cosmetic results, acceptable complication rates and good patient satisfaction.